1971
DOI: 10.1161/01.res.28.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Circus Movement within the AV Node as a Basis for Supraventricular Tachycardia as Shown by Multiple Microelectrode Recording in the Isolated Rabbit Heart

Abstract: Supraventricular tachycardia in an isolated rabbit heart preparation was repeatedly initiated and terminated by carefully timed atrial premature beats. Transmembrane action potentials of AV nodal cells were recorded simultaneously by a "brush electrode" consisting of 10 microelectrodes. Surface electrograms of atrium and His bundle were also recorded. The moments of activation of 54 different AV nodal cells, both during regular driving of the atrium and during tachycardia were ascertained. Premature atrial bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Alternatively, another experimental study provided evidence in favor of an intra-AV nodal reentry circuit. 8 Also, some recent descriptions of the AV node have suggested that the slow and fast pathways exist within the AV node. 9,10 Clinically, Josephson and Miller 11 proposed the concept of intra-AV nodal reentry.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, another experimental study provided evidence in favor of an intra-AV nodal reentry circuit. 8 Also, some recent descriptions of the AV node have suggested that the slow and fast pathways exist within the AV node. 9,10 Clinically, Josephson and Miller 11 proposed the concept of intra-AV nodal reentry.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments using the superfused rabbit AV junction have demonstrated echo beats and even sustained supraventricular arrhythmia within the posterior-inferior right atrium, with the reentrant pathway contained either within or partially outside of Koch's triangle. [5][6][7][8] Little information concerning the anatomic site and functional basis for echo beats and sustained supraventricular arrhythmia has been provided, a result of a complicated 3-dimensional anatomy and the absence of an accepted definition for the dimensions and location of the AV node. Both the mechanism and the site for AVNRT in humans have been presumed to be intra-AV nodal for 20 to 30 years, with a paucity of clinical data supporting this hypothesis.…”
mentioning
confidence: 99%
“…Activation times for intracellular recording were determined at the point of .Tnax. 16 Resting membrane potential was obtained from a DC amplified action potential signal (total IOOX) and stored on a memory oscilloscope. If resting membrane potential deviated by more than 5 mV, the experiment was not used for the determination of action potential variables since we noted some variability inVmax.…”
Section: Methodsmentioning
confidence: 99%